Paradoxical Leadership to Enable Strategic Agility. (May 2014) - Lewis, Marianne W.; Andriopoulos, Constantine; Smith, Wendy K.
Strategic agility evokes contradictions, such as stability-flexibility, commitment-change, and established routines-novel approaches. These competing demands pose challenges that require paradoxical leadership—practices seeking creative, both/and solutions that can enable fast-paced, adaptable decision making. Why is managing paradox critical to strategic agility? And which practices enable leaders to effectively manage tensions? This article describes the paradoxical nature of strategic agility. Drawing from data from five firms, Astro Studios, Digital Divide Data, IBM Global Services Canada, Lego, and Unilever, it proposes leadership practices to effectively respond to these challenges.